2008
DOI: 10.1590/s0037-86822008000100013
|View full text |Cite
|
Sign up to set email alerts
|

Chagas disease as a mechanistic model for testing a novel hypothesis

Abstract: The association between depression and cardiovascular disease is well documented. Nevertheless, the process through which they are linked remains unknown, as does the direction of this relationship. Studies have suggested both that depression is a risk factor for heart disease and that heart disease is a risk factor for depression. A number of studies have established that a relationship exists between depression and inflammation, with alterations in the levels of inflammatory markers (IL-1, IL-6, TNF-alpha an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Besides facing considerable disruption to their psychological well-being, individuals suffering from these disorders are also at considerably greater risk for additional conditions as heart disease and obesity ( Sheps & Sheffield 2001 , Rumsfeld & Ho 2005 ). Depression and other behavioural alterations have been proposed as secondary consequences of the chronic inflammatory chagasic cardiomyopathy ( Mosovich et al 2008 ). Indeed, chronically Colombian-infected C57BL/6 mice also present electrical and functional heart alterations ( Silverio et al 2012 , Pereira et al 2014a , b , 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Besides facing considerable disruption to their psychological well-being, individuals suffering from these disorders are also at considerably greater risk for additional conditions as heart disease and obesity ( Sheps & Sheffield 2001 , Rumsfeld & Ho 2005 ). Depression and other behavioural alterations have been proposed as secondary consequences of the chronic inflammatory chagasic cardiomyopathy ( Mosovich et al 2008 ). Indeed, chronically Colombian-infected C57BL/6 mice also present electrical and functional heart alterations ( Silverio et al 2012 , Pereira et al 2014a , b , 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some papers deal with specific conditions, such as those of pacemaker users, heart failure, or pre-and posttreatment evaluations, and do not describe the profile of QoL in ChD patients. Furthermore, some authors suggest that the putative relation between ChD and depression deserves to be elucidated 37 .…”
Section: Health-related Quality Of Life Of Chagas Diseasementioning
confidence: 99%
“…Reports in the literature indicate that HRQoL is worse for patients with Chagas disease (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)23) . No HRQoL study was found that specifically focused on patients with ChA.…”
Section: Discussionmentioning
confidence: 99%